Improvements in domestic water services in Kelantan: are people willing to pay? - Kamaludin, Mahirah; Abdul Rahim, Khalid; Radam, Alias; Yacob, Mohd Rusli (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study evaluates the willingness to pay by the people in Kelantan for improved domestic water services. Unsatisfactory services by the Kelantan water company threaten heavily household chores and have become a long-standing issue in the state. Excessive water consumption, rapid social and economic growths are putting heavier demands on quality of services and the water company is unable to cope with large populations. This study employs Choice Modelling (CM) method (via Choice Experiment) to examine other possible alternatives in domestic water services. In the CM method, it highlighted four attributes such as water quality (QUAL), water interruption (INT), non revenue water (NRW) and water prices (WP) in its services. Respondents are required to trade off their income for positive changes in the services. Simple and interactions of Conditional Logit (CL) models are estimated to account for heterogeneity in the selected choices of the consumers from options provided in water service attributes. It is interesting to note that of the four attributes considered in this study, reducing the frequency of water interruption becomes a priority for the population in the services. The findings of the study provide important policy implications for stakeholders suggesting that consumer preferences need to be considered in providing efficient services.